Invention - Bender, Lionel (New York : Knopf, 1991)
Photographs and text explore such inventions as the wheel, gears, levers, clocks, telephones, and rocket engines.
Includes index.
Keywords: Inventions -- Juvenile literature; Inventions; Technology